2014
DOI: 10.1111/pce.12275
|View full text |Cite
|
Sign up to set email alerts
|

Role of H2O2 dynamics in brassinosteroid‐induced stomatal closure and opening in Solanum lycopersicum

Abstract: Brassinosteroids (BRs) are essential for plant growth and development; however, their roles in the regulation of stomatal opening or closure remain obscure. Here, the mechanism underlying BR-induced stomatal movements is studied. The effects of 24-epibrassinolide (EBR) on the stomatal apertures of tomato (Solanum lycopersicum) were measured by light microscopy using epidermal strips of wild type (WT), the abscisic acid (ABA)-deficient notabilis (not) mutant, and plants silenced for SlBRI1, SlRBOH1 and SlGSH1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(101 citation statements)
references
References 70 publications
4
92
2
Order By: Relevance
“…DCF and PO1 signals accumulate in the nucleus, as demonstrated by DCF colocalization with Hoechst stain, where ROS plays a role by changing the activity of redox-sensitive transcription factors (Willems et al, 2016). DCF signal has been observed previously in the guard cell cytoplasm (Lee et al, 1999;Kwak et al, 2003;Chen and Gallie, 2004;Watkins et al, 2014;Xia et al, 2014;, but the images within this data set use an Figure 7. Flavonoid mutants have altered stomatal opening in response to light.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DCF and PO1 signals accumulate in the nucleus, as demonstrated by DCF colocalization with Hoechst stain, where ROS plays a role by changing the activity of redox-sensitive transcription factors (Willems et al, 2016). DCF signal has been observed previously in the guard cell cytoplasm (Lee et al, 1999;Kwak et al, 2003;Chen and Gallie, 2004;Watkins et al, 2014;Xia et al, 2014;, but the images within this data set use an Figure 7. Flavonoid mutants have altered stomatal opening in response to light.…”
Section: Discussionmentioning
confidence: 99%
“…Although tomato RBOH mutants are not available, SIRBOH1, a homolog of Arabidopsis RBOHF, has the target of virus-induced gene silencing to demonstrate that there is less CO 2 -and salt stress-induced stomatal closure and that the response to ABA is reduced Yi et al, 2015). Another study showed that brassinosteroid signaling functions through RBOH enzymes to induce stomatal closure (Xia et al, 2014). Together, these studies support the model that tomato guard cell closure requires an ABA-induced ROS burst, but what has not been examined in tomato is whether ROS homeostasis is regulated by antioxidants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBR also caused an increase in E and g s , which was induced by the increase in the W w previously described. The stomatal mechanism is dependent on the water status of the tissue and has a strong influence on gas exchange (Dias and Brüggemann 2010;Xia et al 2014). Afzal et al (2014) evaluated the gas exchange of Vigna radiata plants under a water deficit and also found reductions in P N and g s .…”
Section: Discussionmentioning
confidence: 99%
“…Some species, such as tomato ( Solanum lycopersicum ), lettuce ( Lactuca sativa ), peanut ( Arachis hypogaea ), and apple rootstock ( Malus xiaojinensis and Malus baccata ), show different levels of resistance to Fe deficiency among genotypes (Han et al, 1994, 1998; Wang and Li, 1995; Xu et al, 2009; Sun et al, 2013; Xia et al, 2014). Self-incompatible species, such as apple, have higher levels of genetic variation, and the use of highly heterozygous Malus genotypes allowed us to identify an Fe-efficient woody plant in which to study the role of ROS in the response to Fe deficiency.…”
Section: Introductionmentioning
confidence: 99%